SPONTANEOUS OVARIAN HYPERSTIMULATION SYNDROME - Лариса Егоровна Фетищева; Любовь Никитична Петрич; Светлана Ивановна Елгина; Елена Владимировна Рудаева; Кира Борисовна Мозес; Наталья Степановна Черных; Яэль Центер (The Publishing House Medicine and Enlightenment, 2023)
Ovarian Hyperstimulation syndrome (OHSS) is a rare disease that can lead to fatal complications, almost always associated with the induction of ovulation by gonadotropins or sometimes clomiphene citrate. However, OHSS also occurred in spontaneous ovulatory cycles and rarely in non-pregnant women. The etiology and pathogenesis of spontaneous OHSS are insufficiently studied. In almost all cases, the disease regresses spontaneously and is treated expectantly or conservatively, but with termination of pregnancy or surgical intervention in case of complications. This publication is devoted to the clinical observation of the development of spontaneous ovarian hyperstimulation syndrome.